Comparative study on stomach content analysis of snakehead fish (Channa striata, BLOCH 1793) from the Sibam and Kulim Rivers, Riau Province - Rahma Dhania Salamah; Efawani '; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Snakehead fish (Channa striata) inhabits the Sibam River that has polluted water and the Kulim River that has good water quality. As the quality of water affects the availability of food resources, it may influence the stomach content of the fish. A research aims to understand the stomach content of the fish was conducted on January-March 2017. The Index of Preponderance (IP) was calculated. There were 32 fishes from the Sibam River and 56 fishes from the Kulim River. Results shown that the main food of the snakehead fish was fish, IP value was 89% and 94% in the Sibam and Kulim Rivers respectively. Other types of food present in stomach of the Kulim’s fish were insect, bivalve and crustacean, but there was no crustacean in the Sibam’s fish. Data obtained shown that the water quality affect the availability of the snakehead fish food in general, as the fish food from the Kulim River is more various.Keyword : Sibam River, Kulim River, Stomach Content, Channa striata